Application of a Power Electronic Based Fault Current Limiter (FCL) to Reduce Arc Flash Energy in Electrical Grids with High Short-Circuit Power - Weiland, Manuel; Schön, André; Herold, Gerhard (EPE 2011 - 14th European Conference on Power Electronics and Applications, 2011)
Faults in electrical grids with a high short-circuit power are, among other things, problematic because of electric arcs. As these arc flashes can come along with a high incident energy and so are a risk, both for persons and equipment, finding ways to reduce the incident energy of arcs makes sense. Fault current limiters (FCL) generally offer the possibility to reduce this arc energy. Currently in a research project the application of a certain type of FCL on the reduction of arc energy is investigated. In this paper the results of the first step of this research project, the theoretical examinations, are summarized. Thereby, for a given system with a high short-circuit power a worst-case estimation for the incident energy of arcing faults is aspired to. Furthermore, statements on the possible limitation of this energy via the application of the considered FCL are derived. © 2011 EPE Association - European Power Electr.
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.leen.applic
Keywords: Current limiter; Fault handling strategy; Protection device; Safety; Three-phase system

Control Design for a Power Electronic Based Fault Current Limiter (FCL) - Hahn, Christoph; Weiland, Manuel; Herold, Gerhard (International Conference on Renewable Energies and Power Quality (ICREPQ'12), 2012)
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.contro

Control Strategies for a Power Electronic Based Fault Current Limiter (FCL) in No-Fault Operation - Weiland, Manuel; Hahn, Christoph; Herold, Gerhard (International Conference on Renewable Energies and Power Quality (ICREPQ12), 2012)
Fault current limiters (FCL) in electrical power systems offer the opportunity to reduce short-circuit stresses to the system in the case of faults. But as electrical power systems are normally operated without faults most of the time, FCLs must not have negative effects during these periods of normal operation. The FCL investigated in this paper is based on a 6-pulse current converter. As every other current converter this type of FCL can introduce additional system perturbations in form of higher harmonics. The aim of this work is to develop appropriate strategies to control the FCL in a way that virtually no additional system perturbations are introduced by the FCL under normal no-fault conditions. In electrical three-phase systems this means simply, the controller has to provide sinusoidal current waveform
UnivIS-Import:2015-04-16:Pub.2012.tech.IE.leen.contro_3
Keywords: FCL; converter control; short-circuit; thyristor converter

Ein Beitrag zur Berechnung des unsymmetrischen und transienten Betriebes netzgeführter Stromrichter - Weiland, Manuel (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2013)
UnivIS-Import:2016-07-26:Pub.2013.tech.IE.leen.einbei

Evaluation of power LEDs and their efficiency by driving them with currents typical to switch-mode power supplies - Weiland, Manuel; Schmid, Markus; Kübrich, Daniel; Dürbaum, Thomas (Proceedings of Power Electronics Intelligent Motion Power Quality Conference (PCIM), 2007)
UnivIS-Import:2015-04-16:Pub.2007.tech.IE.leen.evalua

Evaluation on the Efficiency of Power LEDs Driven with Currents Typical to Switch Mode Power Supplies - Schmid, Markus; Kübrich, Daniel; Weiland, Manuel; Dürbaum, Thomas (Conference Record - IAS Annual Meeting (IEEE Industry Applications Society), 2007)
Electronic ballasts are necessary to use light emitting diodes (LEDs) for illuminating purposes powered from the mains. As a consequence this paper shows an examination of two white LEDs considering the resulting losses in luminous efficiency if the LEDs will be driven with different current waveforms as they typically occur in switch-mode power supplies. Therefore it is possible to estimate to which extend more circuitry effort is advisable. © 2007 IEEE.
UnivIS-Import:2015-03-09:Pub.2007.tech.IE.lselek.evalua_4
Keywords: Electronic ballast; General illumination; Power LED

Investigation of Line-Commutated Three-Phase Converters under Voltage Unbalance - Weiland, Manuel; Herold, Gerhard (International Conference on Renewable Energies and Power Quality ICREPQ '10, 2010)
Power converters operated in unsymmetrical three-phase electrical systems will generally work asymmetrically. This introduces disadvantages for the operation of the electrical power system, like non-characteristic harmonics. In the case of controllable power converters, such as thyristor converters, it is possible to operate the converter with asymmetrical firing angles. This offers the opportunity to react on the system’s unbalance optimizing the asymmetrical operation of the converter to lower the disadvantages. In this paper, a method is presented to calculate the behaviour of electrical equipment based on line-commutated current con- verters. Thereby, the operation of the essentially non-linear system is described as sectional continuous linear problem. For its solution an approach with differential equations in the range of space-phasors is used. It is shown to be possible to optimize the unsymmetrical operation with respect to certain quality criteria by using unsymmetrical firing angle
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.invest
Keywords: Power converter; voltage unbalance; converter control; distortion; optimization

Investigation of Line-Commutated Three-Phase Converters with Impedance Unbalance - Weiland, Manuel; Herold, Gerhard (Electric Power Quality and Supply Reliability PQ2010, 2010)
Current converters operated in unbalanced electrical three-phase systems will generally work asymmetrically, which causes the appearance of non-characteristic harmonics and therefore higher distortion levels. In this paper unbalances are considered, that are caused by asymmetrical AC-line short-circuit impedances, which are usually a result of unbalanced transmission lines. In the case of thyristor converters one can react on a given unbalance with asymmetrical firing angles. This offers the opportunity to make the converters operation more balanced und to lower the distortion caused by unbalance. This paper deals with the calculation of a current converter's asymmetrical operation and its optimization by use of asymmetrical firing angles. © 2010 IEEE.
UnivIS-Import:2015-04-16:Pub.2010.tech.IE.leen.invest_2

Investigation of six-pulse three-phase converters in unsymmetrical operation - Weiland, Manuel; Först, Bernhard; Herold, Gerhard (EPE 2009 - 13th European Conference on Power Electronics and Applications, 2009)
Power converters operated in unsymmetrical three-phase electrical systems will generally work asymmetrically. This introduces disadvantages for the operation of the electrical power system, such as non-characteristic harmonics in voltage and current. In this paper, a method is presented to control the behavior of electrical equipment based on line-commutated current converters using unsymmetrical firing angles. Thereby the operation of the essentially non-linear system is described as sectional continuous linear problem. For its solution an approach with differential equations in the range of space-phasors is used. On the basis of a six-pulse line-commutated current converter it is shown to be possible to optimize the unsymmetrical operation with respect to certain quality criteria.
UnivIS-Import:2015-04-16:Pub.2009.tech.IE.leen.invest
Keywords: Converter control; Harmonics; HVDC; Power quality; Three-phase system

Investigation of Three-Phase Thyristor Converters under Generalized Impedance Unbalance - Weiland, Manuel; Herold, Gerhard (International Conference on Renewable Energies and Power Quality ICREPQ, Report 347, 2011)
Line-commutated current converters operated in electrical power systems will work asymmetrically, if the system is not balanced. This asymmetrical operation causes non-characteristic harmonics in the currents and therefore a higher distortion level. As a high distortion level is always disadvantageous, it is worthwhile to find appropriate methods to lower the distortion level by reducing the amplitudes of these non-characteristic harmonics. In this paper, three-phase thyristor converters operated in systems with unbalanced AC-line short-circuit impedances are investigated. To achieve a competent and well-grounded understanding of the problem a suitable method of calculation has been developed. This method firstly offers the opportunity to calculate the operation of line-commutated current converters in an unbalanced three-phase system. Furthermore it offers the opportunity to optimize the operation of the unbalanced system. This optimization is done by balancing the systems operation and reducing the amplitudes of the non-characteristic harmonics using asymmetrical firing angle
UnivIS-Import:2015-04-16:Pub.2011.tech.IE.leen.invest
Keywords: Power converter; unbalance; converter control; distortion; optimization